Knowledge, attitudes, and practices regarding HIV among university students: A comparative cross-sectional study of residents vs. off-campus students. - Mbanjwa, Sibonelo Thanda (Student’s Journal of Health Research Africa, 2025)
Background HIV remains a major public health concern among young adults, particularly within higher education settings. University students’ living arrangements, whether residing on-campus or off-campus, can significantly influence their knowledge, attitudes, and practices (KAP) related to HIV prevention and care. This study aimed to compare HIV-related KAP between students living in university residences and those residing off-campus. Method A cross-sectional study was conducted at a South African university between October 2021 and January 2022. Using stratified random sampling, 400 undergraduate students were selected, comprising 200 on-campus and 200 off-campus residents. Data were collected using a structured, pre-validated KAP questionnaire covering HIV knowledge, attitudes, sexual behaviours, and access to services. Quantitative data were analysed using descriptive statistics, chi-square tests, and logistic regression. Results Participants had a mean age of 21.4 years (SD = 2.1); 52% were female and 48% male. On-campus students demonstrated significantly higher HIV knowledge scores (mean 78%) compared to off-campus students (mean 63%) (p < 0.01). Positive attitudes toward HIV prevention were reported by 85% of on-campus students, compared to 68% of off-campus students (p < 0.05). Risky sexual behaviours, including inconsistent condom use and multiple sexual partners, were more prevalent among off-campus students (42%) than those on campus (25%) (p < 0.01). Engagement with campus-based HIV education programs was notably lower among off-campus students (34%) versus on-campus students (76%) (p < 0.001). Conclusion Living arrangements significantly influence HIV-related KAP among university students, with off-campus students at greater risk due to lower knowledge levels and limited program engagement. Recommendation Targeted HIV outreach for off-campus students, coupled with partnerships with community health organizations, is essential to ensure equitable access to prevention and care.